Kontribusi Pendapatan Usahatani Nilam Terhadap Pendapatan Rumah Tangga Petani di Kecamatan Sampoiniet Kabupaten Aceh Jaya - Nirrah Aiyula; Mujiburrahmad Mujiburrahmad; T makmur (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Patchouli (Progestemon Cablin Bent) is a plantation commodity, one of which has bright prospects in marketing. Income is the acceptance received by the community from every work done, either directly or indirectly in the form of salaries, wages, rent, interest, profits and so on. Contribution is support or share, patchouli farming contribution to family income is the amount of support or income obtained from patchouli farming to the overall income from farming. The purpose of this study is to find out how much income is outside patchouli farming per 6 months in Sampoiniet District, Aceh Jaya Regency and to find out how much patchouli farming contributes to farmer household incomes in Sampoiniet District, Aceh Jaya Regency. This study uses the method of income contribution analysis, farming analysis and the concept of income measurement. The results of this study indicate that the average income of patchouli farming in Sampoiniet District, Aceh Jaya Regency is Rp. 54,713,350 with a contribution of 60%, the average income of non patchouli farming is Rp. 30,032,000 with a contribution of 33%. the average income of non-agricultural businesses is IDR 6,146,000 with a contribution percentage of 7% and the total average household income is IDR 90,891,350 with a percentage contribution of 100%.